Administrative Law Analysis of Governmental Supervision over Online Transportation Application Companies in Indonesia - Hanifatul Fauziah; Eko Nuriyatman; Rustian Mushawirya (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2026)
The rapid growth of online transportation services has transformed the governance of transportation by placing application companies in a strategic position that influences operational standards, service quality, and the relationship between drivers and users. However, the regulatory framework governing governmental supervision of these companies remains unclear, particularly regarding the legal status of application companies as objects of administrative supervision and the mechanisms for enforcing compliance. This study aims to analyze the regulation of governmental supervision and the implementation of supervisory mechanisms over online transportation application companies from the perspective of Administrative Law. This research employs normative legal research using statutory and conceptual approaches. The findings reveal that the Minister of Transportation Regulation Number 12 of 2019 imposes various obligations on application companies, including safety, security, and service responsibilities, yet fails to explicitly designate them as subjects of governmental supervision. This regulatory ambiguity creates legal uncertainty and weakens the effectiveness of supervision. Furthermore, the existing supervisory framework lacks clear procedures, evaluation standards, follow-up measures, and administrative sanctions, resulting in ineffective enforcement. The novelty of this study lies in its examination of online transportation application companies as subjects of administrative supervision and in its identification of the inconsistency between regulatory obligations and supervisory authority within the existing legal framework. The study argues that a comprehensive reconstruction of supervisory norms and enforcement mechanisms is necessary to ensure legal certainty, accountability, and effective governance of online transportation services in accordance with the principles of Administrative Law.